An Input-Output Analysis of the Costs of Air Pollution Control - Cohen, Alan S.; Hurter, Arthur P. (Management Science, 1974)
Pollution control costs ore considered in three categories: (i) costs of control equipment, (ii) costs of switching to cleaner fuels or processes, and (iii) costs to consumers measured by changes in a consumer price index. The sum of type (i) and (ii) are “direct” costs; while (iii) is an “indirect” cost. An input-output model is developed which permits inclusion of both direct and indirect costs in the measure of pollution control costs. It is demonstrated that, when there is at least one firm in the community described by the model required to control its pollution, the prices of all consumer goods will be higher after the imposition of controls than before; and the increase in price will be at least as great as the direct costs of pollution control in the production of each good. If each industry can independently minimize its direct cost of pollution control, then the indirect costs will also be minimized. When shortages of clean fuels are considered, firms and industries cannot all control their emissions optimally. In this case, overall minimization of the direct costs of control will not generally result in minimization of the indirect costs as well. However, a particular kind of weighting of industry by industry direct control costs is developed, such that minimization of this weighted sum results in minimization of indirect costs as well.